Latvijas Republikas nepilsoņu tiesiskais statuss Eiropas Savienībā - Vasiļjeva, Aleksandra (Latvijas Universitāte, 2010)
Darbā ir analizēts nepilsoņu tiesību regulējums Eiropas Savienībā. ES tiesībās Latvijas nepilsoņi savās tiesībās tiek pielīdzināti trešo valstu pilsoņiem un viņu tiesību apjoms var atšķirties atkarībā no dažādiem faktoriem. Darba autore uzskata, ka pašreizēja likumdošana sadrumstalo trešo valstu pilsoņu tiesībās, kas noved pie nevienlīdzīgas attieksmes. Darba tika novērtēta iespēja grozīt Pastāvīgā iedzīvotāja direktīvu, lai panāktu samērīgumu starp Dalībvalstu interesēm un trešo valstu pilsoņu tiesībām. Tika sniegts arī priekšlikums mainīt ES pilsonības koncepciju. Bija apskatīts arī jautājums, vai trešo valstu pilsoņi var būt aizsargāti pret diskrimināciju uz pilsonības pamata saskaņā ar Eiropas tiesībām.

Concerning the fact, that Latvia has joined the EU, more actual question seems to be the legal status of Latvian non-citizens in relation to Community Law. In European Union law non- nationals (aliens) of Latvian Republic are treated as third- country nationals and legal rights of this category of people can differ depending on certain circumstances. The author of the Work is concerned that the law regulating the third country nationals rights is very fragmental and leads to inequality. The author of the Work gives proposals for improvement of such situation by amending the text of Long- term resident directive in order to limit the rights of the Member- States to introduce its own restrictions in the third- country nationals rights of movement. One of the solutions which is observed in this research is the amendment of Treaty and changing the concept of the citizenship of the European Union. Also there were examined whether the third- country nationals can rely on the principle of non- discrimination on the grounds of citizenship.
Legal Status of Aliens of Latvian Republic in European Union
Keywords: Juridiskā zinātne